Calibration of Arduino-based Temperature Sensors for Parabolic Solar Collectors with Phase Change Material - Ahmadi Ahmadi; Adi Setiawan; Gunawati Gunawati; Rozanna Dewi (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2023)
The development of energy storage materials requires facilities for testing the materials' ability to store and release energy effectively. This study focuses on the development and calibration of a temperature measurement system for parabolic solar collectors equipped with heat storage media. We employed type-K thermocouples and MAX6675 modules with Arduino as our measurement tools. The calibration process involved comparing sensor measurements with those obtained from commercially calibrated instruments using seven different test materials. The calibration results demonstrated that our sensors exhibited an error rate ranging from 0.66 to 0.73, indicating their accuracy and suitability for monitoring temperature fluctuations in solar thermal collectors. Pengembangan material penyimpan energi thermal membutuhkan sarana untuk uji coba kemampuan bahan dalam menyimpan dan melepaskan energi. Penelitian ini fokus pada pengembangan dan kalibrasi sistem pengukuran temperatur untuk kolektor surya parabola yang memiliki media penyimpanan panas. Kami menggunakan sensor termokopel tipe-K dan modul MAX6675 dengan Arduino sebagai alat pengukuran. Proses kalibrasi melibatkan perbandingan hasil pengukuran sensor dengan alat komersil yang sudah terkalibrasi pada tujuh bahan uji yang berbeda. Hasil kalibrasi menunjukkan bahwa sensor kami memiliki tingkat kesalahan antara 0.66 hingga 0.73, menunjukkan bahwa sensor kami sudah akurat dan dapat digunakan untuk memonitor perubahan suhu pada kolektor surya termal.